2007
DOI: 10.1016/j.meatsci.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Sheep carcass composition estimated from Longissimus thoracis et lumborum muscle volume measured by in vivo real-time ultrasonography

Abstract: The use of Longissimus thoracis et lumborum muscle (LM) volume measured in vivo by real-time ultrasonography (RTU) to estimate carcass composition was evaluated in 47 female sheep. Animals were scanned over six sites (7th, 9th, 11th and 13th thoracic vertebrae and 2nd and 4th lumbar vertebrae). After slaughter carcass weight (CW) and composition by dissection were determined. RTU volume measurements were calculated by multiplying the LM area at each site by the vertebra lengths. Equivalent measurements to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…(2006) Aloka 500V; 5 and 7.5 MHz Predicting carcass composition Hopkins et al . (2007) Honda HS-1201; 5 MHz Accuracy of RTU measurements and predicting carcass composition Silva et al . (2007a) Aloka 500V; 7.5 MHz Predicting carcass composition Leeds et al .…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…(2006) Aloka 500V; 5 and 7.5 MHz Predicting carcass composition Hopkins et al . (2007) Honda HS-1201; 5 MHz Accuracy of RTU measurements and predicting carcass composition Silva et al . (2007a) Aloka 500V; 7.5 MHz Predicting carcass composition Leeds et al .…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
“…A large number of studies (McEwan et al ., 1989;Silva et al ., 2006a;Teixeira et al ., 2006;Hopkins et al ., 2007;Silva et al ., 2007a;Leeds et al ., 2008;Teixeira et al ., 2008;Thériault et al ., 2009;Emenheiser et al ., 2010;Orman et al ., 2010) have found a significant correlation ( r > 0.6; P < 0.01) between both fat and muscle RTU measurements and the corresponding carcass measurements in those regions. The placement of the probe at reference points must be correct, since SFD and LTL muscles vary significantly over short distances either cranio-caudally (Delfa et al ., 1991;Silva et al ., 2007a) or medium-laterally (Simm, 1983;Korn et al ., 2005). In addition, anatomical distortions arising from the position of the animals and skin flexibility may also contribute to discrepancies between RTU and carcass measurements (Thwaites, 1984;Leeds et al ., 2008).…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The BW variable is the most important measurement for predicting muscle weight (Shelton et al, 1977;Jones et al, 1982;Kempster et al, 1982a;Fortin and Shrestha, 1986;Silva et al, 2007), and the inclusion of ultrasound measurements normally provides only a little improvement in the accuracy of the prediction (Leymaster et al, 1985). However, the present results showed that narrow ranges of BW did not offer much as a predictor of the carcass composition of Ternasco lambs because many factors affect the rate and onset of fattening in meat animals, in agreement with , Berg et al (1996), and Puntilla (1986).…”
mentioning
confidence: 99%
“…The use of ultrasound in determining subcutaneous fat thickness and ribeye area would represent an excellent tool for the generation of models that estimate muscle-tofat ratios prior to slaughter, which would allow producers to sell animals with pre-defined carcass profiles (SILVA et al, 2007).…”
Section: Introductionmentioning
confidence: 99%